PG41 COVID-19 rapid crisis response using multi-disciplinary paediatric simulation. (10th November 2020) - Ranaweera, Melanie; Lau, Sinny; Evans, Katie; Whitaker, Matthew
Abstract : Background: The COVID-19 pandemic is an unknown territory, creating new challenges for its workforce. As COVID-19 became widespread, the RCPCH (royal college of paediatrics and child healthcare) advocated simulation as an efficient method to instil best practices in these unique times. 1 2 Early on in the crisis, we rapidly developed multi-disciplinary low fidelity simulation, looking at the clinical journey of a COVID-19 suspected paediatric patient and salient COVID-19 focused aspects of their care. Post-simulation feedback demonstrated 100% of staff felt more confident in all areas of COVID-19 preparation. In addition, it unearthed new ideas to improve care of COVID-19 suspected patients. 2 Method: A low fidelity scenario was created with small groups of up to four people, enabling social distancing. Being low fidelity it was easy to implement efficiently, vital at a time whereby skilling up quickly was a must. The simulation lab mimicked our unit, simulating the patient's admission, transference and deterioration to the ward. The scenario practiced donning and doffing personal protection equipment (PPE), discussions regarding full and standard PPE; concept of clean and contaminated areas; safe handling of patient' samples; aerosol generating procedures, ideal patient transfer and resuscitation. We trained 45 staff members (6 consultants, 24 junior doctors, 1 ward manager, 5 ED (emergency department) nurses and 9 paediatric ward nurses) within 4 days, in one and a half hour sessions. Result: A pre- session questionnaire assessed their confidence levels in RCPCH recommended COVID-19 related skills and knowledge. This was re-evaluated immediately following the session and results showed 100% of staff felt more confident in all areas (figure 1 ). Discussion and Recommendation: Time was allocated for discussions between ED and ward staff. This highlighted better communication was required between our ED and ward, as where best to place admitted patients according to their COVID-19 risk. This is now a mandated component of the admission handover. ED staff had an accessible location of full PPE for emergencies, which triggered the ward staff to create their own, 'full PPE emergency grab bag'. It was also reflected that it would be useful to have a COVID-19 senior lead during this time, to help keep staff up to date with the constantly changing guidelines and policies we were facing during this uncertain time. We highly recommend the use of multidisciplinary COVID-19 simulation as part of robust preparations for paediatric units during this unfamiliar time, as well as to help generate bespoke unit improvements. 2 References: RCPCH Health Policy Team. 2020. COVID-19 Guidance for paediatric emergency and acute settings. Available at : https://www.rcpch.ac.uk/resources/covid-19-guidance-paediatric-services#acute-and-emergency-settings ( Accessed 7th July 2020) Weissman G, et al. Locally informed simulation to predict hospital capacity needs during the COVID-19 Pandemic. Annals of internal medicine 2020;173 (1):pp. 21–28.